Social time and generational (mis)matches. - Lamas, Maria Cristina; Lamas, Ana María (Facultad de Psicología (Universidad Nacional de La Plata, Argentina), 2019)
The purpose of this investigation report is to analyze social time and its relation with generational (mis)matches, in regards to ICTs. For it, a bibliographical revision on the topic of ways of thinking time was made: objective, biographical-subjective, social and with reference to generation and generational consciousness. Colective temporal representations made by social subjects in different time periods were studied. Aspects that were taken into consideration were the various ways in which plural social time is represented and expressed, producing generational (mis)matches. From the association of variables, the impact of acceleration and temporal desynchrony were highlighted in the "Gutenberg" and "Zuckerberg" generations. In conclusion, despite the discrepancy in temporal consciousness between the youth and the elderly, it is possible to articulate their generational temporalities in a new social time, integrating both of them with course and direction.